The asbestos survey: mortality among asbestos workers 1971-2005 - Harding, Anne-Helen; Frost, Gillian (Sudbury, 2009)
"The Asbestos Survey was established to monitor the long-term health of workers covered by regulations to control occupational exposure to asbestos. The aim of this report was to provide an updated analysis of mortality among asbestos workers, to investigate which causes of death were associated with exposure to asbestos, and to undertake a more detailed analysis of the stripping/removal workers. From 1971, workers were recruited during initially voluntary and later statutory medical examinations. During the medical, a brief questionnaire was completed, and participants were then flagged for death registrations. There were 15,496 deaths among the 98,912 workers included in the analysis. All cause mortality was significantly higher than in the general population. Known associations between asbestos exposure and mortality from lung, peritoneal and pleural cancers, mesothelioma and asbestosis were confirmed, and some evidence of associations with stroke and stomach cancer mortality were observed. Limited evidence suggested that asbestos-related disease risk may be lower among those first exposed in more recent times. Among the removal workers, deaths were elevated for all causes, all cancers including lung cancer, mesothelioma, and circulatory disease. Spending more than 40 hours per week in a stripping enclosure increased the risk of all cause, circulatory disease, and ischaemic heart disease mortality. However the different dust suppression techniques and respirator types did not affect mortality rates. Longer follow-up will allow the impact of recent regulations on the health of asbestos workers to be assessed."